2019
DOI: 10.1002/jcb.29355
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐218‐5p relieves postmenopausal osteoporosis through promoting the osteoblast differentiation of bone marrow mesenchymal stem cells

Abstract: MicroRNAs (miRs) are short noncoding RNAs that play key regulatory roles in osteoblast differentiation. In this study, the specific regulatory roles of miR‐218‐5p on postmenopausal osteoporosis (PMOP) were investigated. The mouse model of PMOP was established by bilateral ovariectomy, and the injection of miR‐218‐5p mimics significantly relieved PMOP degree. Then, bone marrow mesenchymal stem cells (BMMSCs) isolated from PMOP mice were induced into osteoblasts. When compared with normal BMMSCs, PMOP BMMSCs exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Bioinformatic analysis showed that the COL1A1 3’-UTR contains binding sites for miR-126-5p and miR-218-5p (Fig. 5 C), consistent with previous studies [ 25 ]. To verify the endogenous mutual interactions between COL1A1 and both miR-126-5p and miR-218-5p, we constructed COL1A1 3’-UTR WT and COL1A1 3’-UTR MUT plasmids.…”
Section: Resultssupporting
confidence: 91%
“…Bioinformatic analysis showed that the COL1A1 3’-UTR contains binding sites for miR-126-5p and miR-218-5p (Fig. 5 C), consistent with previous studies [ 25 ]. To verify the endogenous mutual interactions between COL1A1 and both miR-126-5p and miR-218-5p, we constructed COL1A1 3’-UTR WT and COL1A1 3’-UTR MUT plasmids.…”
Section: Resultssupporting
confidence: 91%
“…Multiple miRNAs regulate the osteogenic differentiation of BMMSCs [40]. For example, microRNA-218-5p targets COL1A1 to promote osteogenic differentiation of OVX-BMMSCs in vitro [41]; while microRNA-145 suppresses the osteogenic differentiation of human BMMSCs [42]. In this study, RNasepretreated SHED-EVs attenuated the SHED-EV-mediated rescue of Tert-associated telomerase activity in recipient BMMSCs.…”
Section: Shed-evs Into Bmmscs Of Recipient Ovx Micementioning
confidence: 57%
“…This involves reduced bone mass with excessive activation of osteoclasts (e.g., Paget's disease) commonly seen in osteoporosis and bone metastases (e.g., multiple myeloma) (Tsukasaki and Takayanagi, 2019). In cases with postmenopausal osteoporosis, bone mass loss is mainly caused by reduced estrogen accompanied by increased osteoclasts and elevated bone resorptive activity (Kou et al, 2019). In this study, we demonstrated that BA in mice with osteoporosis induced by OVX prevented bone loss.…”
Section: Discussionmentioning
confidence: 63%